Analisis Nilai-Nilai Multikultural pada Buku Teks Pelajaran Agama Katolik dan Budi Pekerti Kurikulum 2013 - R.F. Bhanu Viktorahadi; Mohammad Taufiq Rahman; Muhtar Solihin (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
This study discusses the multicultural value content in the 2013 Textbook of Catholic Religious Education and Curriculum Ethics to describe and analyze various themes and characteristics of multicultural values in the Textbook. Besides, this study also aims to describe and analyze dialectics and how the Catholic Church evangelizes multicultural values in the textbooks discussed. Religious education includes the characteristics and levels of multicultural values that officially reveal the Church to proclaim multicultural values. This study is literature research using content analysis methods, and conceptual analysis approaches to the textbooks discussed. The results showed that there was a multicultural value contained in it. Based on this analysis, this study has two conclusions that summarize the achievement of its objectives. First, there are various multicultural themes and characteristics in the 2013 Curriculum Textbook of Religion and Ethics Education. Second, dialectics and the way the Catholic Church organizes the preaching of multicultural values in the 2013 Curriculum Religion and Ethics Textbook. This study can contribute to developing the concept and policies regarding the teaching of multiculturalism in Indonesia, a pluralist country, to become a model for similar countries.